2016
DOI: 10.1007/s10096-016-2876-5
|View full text |Cite
|
Sign up to set email alerts
|

Rapid MRSA PCR on respiratory specimens from ventilated patients with suspected pneumonia: a tool to facilitate antimicrobial stewardship

Abstract: 1Purpose: Methicillin-resistant Staphylococcus aureus (MRSA) is an important cause of 2 pneumonia in ventilated patients. Our objective was to evaluate the GeneXpert 3 MRSA/SA SSTI Assay (Xpert MRSA/SA) (Cepheid, Sunnyvale, CA) for use in lower 4 respiratory tract (LRT) specimens for rapid MRSA detection and to determine the 5 potentially saved antibiotic-days if a culture-based identification method was replaced 6 by this assay. 7 Methods:Remnant LRT samples from ventilated patients submitted to the 8 microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…The high sensitivity and negative predictive value we observed is consistent with prior studies of similar PCR technology in lower respiratory tract samples. [20][21][22][23][24] Leone et al 22 reported technical failures in up to 10% using the Cepheid Nasal Complete assay. In the assay validation portion of our study, only 3.2% of the MRSA/SA SSTI assays initially yielded indeterminate results, but an unambiguous result was achieved when run a second time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high sensitivity and negative predictive value we observed is consistent with prior studies of similar PCR technology in lower respiratory tract samples. [20][21][22][23][24] Leone et al 22 reported technical failures in up to 10% using the Cepheid Nasal Complete assay. In the assay validation portion of our study, only 3.2% of the MRSA/SA SSTI assays initially yielded indeterminate results, but an unambiguous result was achieved when run a second time.…”
Section: Discussionmentioning
confidence: 99%
“…Use of RPCR in BAL has been shown to detect both MRSA and methicillin-sensitive S aureus (MSSA) with a high negative predictive value. [20][21][22] Retrospective analyses from two academic medical centers estimated that vancomycin and linezolid utilization in mechanically ventilated patients with pneumonia could be decreased significantly by using RPCR on BAL 23,24 ; however, retrospective analyses cannot accurately predict actual clinical response to diagnostic testing results, particularly if safety is a concern.…”
mentioning
confidence: 99%
“…These tests have the potential to reduce the duration of broad-spectrum empirical antibiotic therapy by identifying pathogenic organisms or specific antibiotic resistance markers 2 to 3 days sooner than routine methods. Specifically, rapid molecular detection of methicillin-resistant S. aureus (MRSA) in respiratory specimens has been associated with a potential 60% to 80% reduction in anti-MRSA antibiotic days and a total savings of Ͼ$60,000 in antibiotic cost annually (10). Multiplexed molecular tests, including the ePlex RP (GenMark Diagnostics) and the BioFire FilmArray Respiratory 2 (RP2) panel (BioFire Diagnostics), enable broad detection of viral pathogens in respiratory specimens but identify only a few bacteria, including Mycoplasma pneumoniae, Chlamydia pneumoniae, and Bordetella species (11).…”
mentioning
confidence: 99%
“…A rapid test sensitivity equivalent to culture for pathogen detection is easier to achieve than the molecular diagnosis equivalent of culture-based antibiotic susceptibility. The lowest-hanging fruit may be Staphylococcus aureus, where a single mutation predicts methicillin resistance (26,49). Determining antibiotic susceptibility by a rapid test for Pseudomonas aeruginosa or other MDR pathogens is much more complex (50).…”
Section: The Hope Of Rapid Diagnostics Is Currently Unfulfilledmentioning
confidence: 99%